FORMULATION OF MARKETING STRATEGY WITH SWOT ANALYSIS METHOD ON MEYCOOKIES MSMES IN SUMBERSARI, JEMBER REGENCY - Indrayanti, Latri; Izzudin, Ahmad; Rahayu, Jekti (Dynamic Management Journal, 2024)
This study aims to initiate a new marketing strategy for Meycookies by applying a SWOT analysis approach. The study adopted a descriptive qualitative approach, where data was collected through interviews and documentation. Speakers were selected using purposive sampling techniques and the validity of the data was tested through source triangulation. The results of the SWOT analysis show that Meycookies has the power that allows it to take advantage of existing opportunities. This indicates that the company is in a competitive and strong position, so it needs appropriate strategies to develop its business and maintain its growth.